The Role of Muhammadiyah Institution Towards Muslim Minority in West Papua - Wekke, Ismail Suardi; Arif, Beja; Zubair, Andi; Wardi, Moh. (Jurnal Ilmiah Peuradeun, 2019)
Muhammadiyah is known as Islamic organization pioneering modern educational and social movement. Recently, Muhammadiyah education has experienced rapid development, yet there are still many problems and challenges to overcome in order to continue competing and giving the best for the society. The aim of this research was to figure out the role of Muhammadiyah in conducting dakwah bil hal movement in education and social environment in Sorong City, Papua. By using qualitative method and in-depth interview and also field research, this study found out that bil hal Muhammadiyah Movement in Sorong City, Papua has given significant impact on the society, especially in education from Kindergarten to University level. Meanwhile, in the social field, Muhammadiyah in Sorong City had built orphanage for boys and girls. However, in terms of management of organizational governance, Muhammadiyah needs to strengthen the solidity between regional leaders, optimization of autonomous assemblies and organizations as a power base to support maximization of dakwah bil hal Muhammadiyah movement in the future, especially in education and society.